Literature Study : Histopathology Analysis of Rabies Disease (2014 - 2022) - Andadari, Afifah Yudining Dwi; Pratama, Dyah Ayu Oktavianie A.; Hardian, Andreas Bandang; Untari, Handayu (Journal of Applied Veterinary Science And Technology, 2024)
Background: Rabies is a contagious and zoonotic disease caused by Lyssavirus, a neurotropic, negative-sense, single-stranded RNA virus. Rabies infects most mammals through the transmission of saliva from a rabid animal that enters the body of a healthy animal through an open wound, bite, scratch, or direct contact. A post-mortem diagnosis and evaluation are crucial for establishing regional statistical data in order to design a robust strategy for combating rabies. Histopathology has long been known to be an invaluable source of information regarding the destructive impact of rabies in nervous tissue. In addition to other ante-mortem evaluations, a correlation between clinical signs, gross pathological findings, and histopathological findings must be established to achieve the maximum target of combating rabies. Purpose: This study aims to analyze and compare gross pathological findings and histopathological findings in the literature published between 2014 and 2022. Methods: A comparison between gross pathological findings and histopathological findings was conducted on case studies from 2014 to 2022. Anamnesis and clinical signs were obtained as supporting data. The findings were presented as percentage to identify the predominant pathological signs. Results: A review of four case studies revealed that paralysis, hyperesthesia, gait abnormality, and muscle tremor were the most commonly observed signs (50%). Only two case studies revealed gross pathological findings, including meningeal congestion and cerebellar hemorrhage. Eight studies identified the intracytoplasmic negri body in Purkinje cells as the most commonly observed histopathological finding (100%). Conclusion: The primary clinical signs and gross pathological findings associated with rabies are typically regarded as non-specific. Histopathology revealed the intracytoplasmic Negri body in Purkinje cells as the most commonly observed finding (100%).